Transformasi Manajemen SDM dalam Membangun Budaya Kerja Produktif - Faiz Rahmawati (https://journal.metanusantara.com/jenius/index.php/jem, 2024)
Transformation of Human Resources (HR) management is key to addressing the challenges of a productive work culture in organisations. Key strategies implemented include improving the recruitment system, developing training programmes and continuous learning, and implementing an effective performance management system. Training programmes not only enhance employee skills but also attract top talent, improve retention, and strengthen the culture of innovation within the organisation.In addition, building a productive work culture through transparent communication and team building activities has been shown to improve collaboration, morale and employee engagement. The implementation of reward and recognition programmes also plays a role in maintaining motivation and improving individual and team performance.While challenges such as resistance to change remain, effective communication approaches, management support, and employee engagement in the transformation process are key solutions. By implementing the right strategies, organisations can create a more dynamic, innovative and competitive work environment to achieve long-term sustainability.